Self-efficacy and career intention: Uncovering the underlying processes - Md. Sohel Chowdhury; Md. Shakhawat Hossain; Md. Alamgir Hossain; Renhong Wu (PLoS ONE, 2025)
This study aims to suggest and empirically evaluate a conceptual framework that investigates the association of career self-efficacy with career intentions, emphasizing on the specific and sequential mediating mechanisms of two psychological constructs: person-environment (P-E) fit and career attitudes. Relationships among the constructs were hypothesized based on the relevant literature and were examined with AMOS and SPSS Process Macro using survey data collected from a sample of 341 job seekers in Bangladesh. Results showed that P-E fit and career attitudes each partially mediated the relationship between career self-efficacy and career intentions. Noticeably, both the mediators, together in sequence, completely mediated the above relationship. In light of the ensuring chain mediating role of P-E fit and career attitudes, a thorough understanding of the effects of self-efficacy on career intentions not only contributes to the existing literature, but also provides notable implications for career counselors and HR managers in today’s competing firms.